2000
DOI: 10.1074/jbc.m907658199
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Human gp130 at Ser-782 Adjacent to the Di-leucine Internalization Motif

Abstract: The receptor for leukemia inhibitory factor (LIF) consists of two polypeptides, the LIF receptor and gp130. Agonist stimulation has been shown previously to cause phosphorylation of gp130 on serine, threonine, and tyrosine residues. We found that gp130 fusion proteins were phosphorylated exclusively on Ser-782 by LIF-and growth factor-stimulated 3T3-L1 cell extracts. Ser-780 was required for phosphorylation of Ser-782 but was not itself phosphorylated. Ser-782 is located immediately Nterminal to the di-leucine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…S7). The role of phospho-S782 in gp130 was first documented in 2000 to downregulate gp130 cell surface expression (5). Recently, it has been reported that phospho-S782-associated downregulation of gp130 cell surface expression is mediated by immediate internalization (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S7). The role of phospho-S782 in gp130 was first documented in 2000 to downregulate gp130 cell surface expression (5). Recently, it has been reported that phospho-S782-associated downregulation of gp130 cell surface expression is mediated by immediate internalization (46).…”
Section: Discussionmentioning
confidence: 99%
“…Ligand binding induces the association of gp130 with a cytokine-specific receptor-a chain, followed by the activation of downstream signaling cascades including JAK/STAT, RAS/ RAF/MAPK, and PI3K/AKT pathways (4). It has been shown that phosphorylation of gp130 at Ser782 downregulates cell surface expression of gp130 (5,6). As a ubiquitously expressed receptor, gp130 is involved in a wide range of important biologic processes including inflammation, autoimmunity, cancer (7), stem cell maintenance, and embryonic development (8).…”
Section: Introductionmentioning
confidence: 99%
“…A similar motif is contained in the cytoplasmic tails of CD3g, gp130, and CD4. Phosphorylation of an upstream serine and the interaction of the two leucines with clathrin-associated adapter protein AP-2 complexes are required for endocytosis [37][38][39]. As in WC1, the internalization motif in the CD4 cytoplasmic tail is located in a predicted alpha-helix.…”
mentioning
confidence: 99%
“…The other receptor subunits, gp130 and OSMR␤, do not possess a phosphorylation site for ERK 1/2 and, thus, do not appear to be appreciably influenced by activated ERK. However, serine 782 of gp130 located in the cytoplasmic domain has been described as being phosphorylated and directing the cell surface expression of the receptor subunit (14). The kinase for this modification is still unknown.…”
mentioning
confidence: 99%